The Euro Crisis From the Perspective of the Preceding Debates on Fixed versus Flexible Exchange Rates and the European Currency Union - Rudolf Richter (Credit and Capital Markets – Kredit und Kapital, 2013)
The Euro Crisis from the Perspective of the Preceding Debates on Fixed versus Flexible Exchange Rates and the European Currency Union The development of the European Monetary Union is related to Milton Friedman"s critique of the Bretton Woods System that started a vigorous debate about "fixed versus flexible exchange rates." This paper briefly contrasts the arguments pro and con flexible exchange rates at this time. After the breakdown of the Bretton-Woods-System the exchange rate debate was replaced by a somewhat less vigorous discussion on the desirability and drafting of a European Monetary Union (EMU). Predictions of proponents and opponents of EMU are briefly described, and it is shown that specific investments of contractual parties play an important role that may invite ex post opportunistic behaviour of contractual parties – a central problem of the New Institutional Economics in the style of Oliver Williamson. Formation of "unified governance" (integration) is the adequate answer. However, to become a coherent economic unit based on strict and enforceable rules is a more complicated matter for the integration of states than for the integration of firms – because to work in the long term, EMU has to be a self-enforcing entity. That demands not only the transfer of formal sovereign powers to some centre but also its supplementation by informal or ideological European integration, i. e., by the achievement of some mutual consent among the inhabitants of Euroland regarding not least their attitude towards monetary and fiscal policy – so to speak as modern answer to the centuries-old problem of European Equilibrium – an ambitious target that can be achieved neither overnight nor easily. (B52, F15, F31, F33, F34) – – Die Euro-Krise aus der Perspektive der Debatten über feste versus flexible Wechselkurse und über die Europäische Währungsunion Die Entwicklung der Europäischen Währungsunion ist im Zusammenhang mit der vorausgegangenen Kritik von Milton Friedmans am Bretton Woods System zu sehen, die eine lebhafte Debatte zum Thema "feste versus flexible Wechselkurse" auslöste. Die Debatte wurde kurz nach Zusammenbruch des Bretton Woods Systems von der Diskussion über die Wünschbarkeit und Realisierung einer Zone fester Wechselkurse innerhalb Europas fortgesetzt. Beide Debatten werden von uns skizziert und gezeigt, dass der Übergang zu einer internationalen Währungsgemeinschaft vertragsspezifische Investitionen erfordert, die einzelne Vertragsparteien zu opportunistischem Verhalten einladen können. Genau das ist ein zentrales Problem der Neuen Institutionenökonomik vom Typ der Transaktionskostenökonomik von Oliver Williamson. Seine Antwort lautet: Zum Schutz gegen ex-post opportunistisches Verhalten von Vertragspartnern sollen sich die Parteien zu einer Union unter einheitlicher Führung zusammenschließen – zu "unified governance". Für souveräne Staaten ist dieser Schritt jedoch problematischer als für Einzelpersonen oder Unternehmungen, deren Verträge nationalem Rechtszwang unterliegen. Die Europäische Währungsunion – ein internationaler Vertrag – muss dagegen selbstdurchsetzend sein. Das erfordert mehr als nur die Übertragung nationaler Souveränitätsrechte an eine europäische Zentralstelle. Es verlangt dazu die Entwicklung gegenseitigen Einvernehmens der Bürger aller Mitgliedsstaaten hinsichtlich ihrer wirtschaftspolitischen Vorstellungen – sozusagen als zeitgemäße Antwort auf das jahrhundertalte Problem des europäischen Gleichgewichts – ein Ziel das weder leicht noch im Eilverfahren erreicht werden kann. (B52, F15, F31, F33, F34)
Keywords: 330